Accounting Discretion, Corporate Governance, and Firm Performance* - Bowen, Robert M.; Rajgopal, Shivaram; Venkatachalam, Mohan (Contemporary Accounting Research, 2008)
We investigate whether accounting discretion is (i) abused by opportunistic managers who exploit lax governance structures, or (ii) used by managers in a manner consistent with efficient contracting and shareholder value-maximization. Prior research documents an association between accounting discretion and poor governance quality and concludes that such evidence is consistent with abuse of the latitude allowed by accounting rules. We argue that this interpretation may be premature because, if such association is indeed evidence of opportunism, we ought to observe subsequent poor performance, ceteris paribus. Following Core et al. (1999) we conduct our analysis in two stages. In the first stage, we extend the prior literature and again find a link between poor governance and managers' accounting discretion. However, in the second stage we fail to detect a negative association between accounting discretion attributable to poor governance and subsequent firm performance. This suggests that, on average, managers do not abuse accounting discretion at the expense of firms' shareholders. Rather, we find some evidence that discretion due to poor governance is positively associated with future operating cash flows, which suggests that shareholders may benefit from earnings management, perhaps because it signals future performance.